Identification of aerosol type over the Arabian Sea in the premonsoon season during the Integrated Campaign for Aerosols, Gases and Radiation Budget (ICARB) - Kalapureddy, M.C.R.a; Kaskaoutis, D.G.b; Ernest Raj, P.a; Devara, P.C.S.a; Kambezidis, H.D.b; Kosmopoulos, P.G.c; Nastos, P.T.c (Journal of Geophysical Research Atmospheres, 2009)
A discrimination of the different aerosol types over the Arabian Sea (AS) during the Integrated Campaign for Aerosols, Gases and Radiation Budget (ICARB-06) is made using values of aerosol optical depth (AOD) at 500 nm (AOD500) and Ångström exponent (α) in the spectral band 340-1020 nm (α340-1020). For this purpose, appropriate thresholds for AOD500 and α340-1020 are applied. It is shown that a single aerosol type in a given location over the AS can exist only under specific conditions while the presence of mixed aerosols is the usual situation. Analysis indicates that the dominant aerosol types change significantly in the different regions (coastal, middle, and far) of AS. Thus the urban/industrial aerosols are mainly observed in coastal AS, the desert dust particles occur in the middle and northern AS, while clear maritime conditions mainly occur in far AS. Spectral AOD and Ångström exponent data were analyzed to obtain information about the adequacy of the simple use of the Ångström exponent and spectral variation of a for characterizing the aerosols. Using the least squares method, α is calculated in the spectral interval 340-1020 nm along with the coefficients a1 and a2 of the second-order polynomial fit to the plotted logarithm of AOD versus the logarithm of wavelength. The results show that the spectral curvature can effectively be used as a tool for their discrimination, since the fine mode aerosols exhibit negative curvature, while the coarse mode particles exhibit positive curvature. The correlation between the coefficients a1 and a2 with the Ångström exponent, and the atmospheric turbidity, is further investigated. Copyright 2009 by the American Geophysical Union.
Keywords: aerosol composition; Aerosol optical depths; aerosol property; Aerosol types; Algebra; Arabian Sea; Atmospheric aerosols; Atmospheric turbidity; Budget control; Coarse mode particles; Desert dust; dust; Indian Ocean; integrated approach; Least squares methods; marine atmosphere; Negative curvature; Pre-monsoon; Radiation budget; Second-order polynomial; spectral analysis; Spectral band; Spectral variation; Turbidity; wavelength